Old English Items in London, British Library, MS Cotton Tiberius C. i - Morgan, Hollie (New Medieval Literatures, 2011)
Abstract London, British Library, MS Cotton Tiberius C i is a composite manuscript containing scientific and religious texts, made up of two independent elements. The manuscript is predominantly Latin, but each of the elements contains a small amount of Old English: the first contains glosses of the names of the winds; the second, some short homiletic texts, the Pater Noster and an Old English Creed. This essay explores the Old English instances and discusses possible explanations for their presence, arguing that their production may have been of more use to the writers than to any imagined audience.